Proceedings of the 23rd International ACM SIGACCESS Conference on Computers and Accessibility 2021
DOI: 10.1145/3441852.3476469
|View full text |Cite
|
Sign up to set email alerts
|

Developing Accessible Mobile Applications with Cross-Platform Development Frameworks

Abstract: We illustrate our experience, gained over years of involvement in multiple research and commercial projects, in developing accessible mobile apps with cross-platform development frameworks (CPDF). These frameworks allow the developers to write the app code only once and run it on both iOS and Android. However, they have limited support for accessibility features, in particular for what concerns the interaction with the system screen reader.To study the coverage of accessibility features in CPDFs, we first syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Second, these studies provide valuable insights into the limitations of UI frameworks as they are used by sighted developers [29]. Sighted developers have found that Xamarin [30] and React Native [4] do not expose all the accessibility APIs, making it difficult to create fully accessible mobile applications [31]. Similarly, the web frameworks, Angular, Vue, and React, do not notify sighted developers about accessibility violations [32].…”
Section: B Accessibility Of Ui Developmentmentioning
confidence: 99%
“…Second, these studies provide valuable insights into the limitations of UI frameworks as they are used by sighted developers [29]. Sighted developers have found that Xamarin [30] and React Native [4] do not expose all the accessibility APIs, making it difficult to create fully accessible mobile applications [31]. Similarly, the web frameworks, Angular, Vue, and React, do not notify sighted developers about accessibility violations [32].…”
Section: B Accessibility Of Ui Developmentmentioning
confidence: 99%
“…In react native, JavaScript is used to create the applications, therefore, the interpreted technique has been used here. In this approach, JavaScript code defines generalized widgets not specific-platform widgets, but under the hood, each widget has an associated widget in each platform supported by the framework (Mascetti et al 2021). interaction between the application side and platform side has been done by the bridge, which converts the generalized widgets to the platform-specific widgets depending on the platform on which the application running, therefore, the rendering process happens on the platform side, not an application.…”
Section: B Tools and Framework For Cross-platform Solution 1) React N...mentioning
confidence: 99%